Diseño e Implementación de un Sistema de Monitoreo y de Activación Remota para Equipos de Telecomunicaciones de la Empresa NODO CIA. LTDA. Utilizando Tecnología GPRS de Comunicaciones Móviles en la Zona 7 - Mendoza Montaño, Freddy Israel (2024)
The following final assignment emphasizes the investigation according to the problems present in the company NODO CIA LTDA. It has a series of drawbacks in terms of the electrical conditions of its network equipment specifically for the Villonaco station where they are affected by extreme weather conditions. Under this context, the research starts by defining a mobile communication technology that uses the GPRS coverage, present in the area, in such a way that a compilation of information from different authors begins where a GPRS system has been successfully implemented, from where The theoretical knowledge, contributions and background on the structure of a GPRS system, its architecture uses nodes and a centralized server is obtained, in turn the use, advantages and disadvantages of the HTTP protocol as a method of communication and writing of variables are considered. towards the database. After the investigation stage is over, it is necessary to proceed and carry out the design stage through the selection of hardware, the Arduino Mega 2650 microcontroller, the SIM808 GPRS communication card, the DHT22 sensor for humidity and temperature and the ZMPT101B AC Voltage sensor and the Relay Module are defined. of a 5V channel, these components present a node of easy implementation, wide scalability and use of monitoring variables according to the company's requirements. Finally, the implementation of a final prototype with a backup power system is established, with highly favorable results in its integration with the server, adding to the company a system with security and functionality on the activation / deactivation of energy in its network equipment. Keywords: GPRS, SIM808, HTTP, Arduino.